Curvas parametrizadas, ciclóides, experimentos e aplicações - Venceslau, Allisson Wesley do Nascimento (2015)
This work aims at presenting methodological referrals able to make mathematics teaching more enjoyable and interactive. In this sense, the work that will be developed here will address the study of some special curves like the Agnesi Curve, the Epicycloid, the Hypocycloid and will focus in greater depth the study of Cycloid addressing its main properties with an emphasis on Tautochrone and Brachistochrone. All work performed in this study shows that mathematics can play an important role in the classroom, helping to develop the learning of other disciplines thanks to allied experimental practices to the development of interdisciplinary content. In the literature there is much talk on interdisciplinarity, but most texts do not show how it can be done, that is, little is done really. This paper describes the content and shows how to perform integrative activities that will improve the teaching of other sciences and allows students to develop other skills (in addition to mathematical reasoning). This work does not end here, it is the rst step to other studies that improve the teaching of mathematics, especially geometry. Introduce the content so that the curiosity of the student is instigated is a big step in the teaching of this discipline. This is the objective of this work, arouse the curiosity of those involved through experimental practices without so little put aside theoretical part.